Empowering Community Participation in Funding Education at MA Queen Al Khotijah Cilacap - Slamet Pamuji (MultiTech Publisher, 2023)
This study aims to describe the empowerment of community participation in financing education at MA Queen Al Khotijah Cilacap. This research is a descriptive research with a qualitative approach. The informants of this research are school principals and school treasurers. Data collection methods used in the form of interviews, observation, and documentation. The data validity test was carried out by triangulation of techniques and sources. Data were analyzed qualitatively with Miles and Huberman's interactive model. The results of the study show that: The determination of education funding at MA Queen Al Khotijah gathers the guardians of the students to sit together and have deliberations. In this deliberation, the Supreme Court explained plans for MA funding needs, especially for the payment of teachers' and assistants' salaries. Then, the administrators and the student's guardian agree and make a joint decision on the nominal amount that must be paid by the student's guardian each month. Not only that, as a form of report and evaluation, the administrators also report to the student's guardian regarding monthly income and expenses during the student guardian meeting, especially those related to paying the salaries of teachers and assistants. In addition, there are also several donors who provide funding for MA apart from BOS funds